2015
DOI: 10.1089/ten.tea.2014.0177
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of Polycaprolactone Scaffolds with Hyaluronic Acid and β-TCP Facilitates Migration and Osteogenic Differentiation of Human Dental Pulp Stem CellsIn Vitro

Abstract: In this study, we sought to assess the osteogenic potential of human dental pulp stem cells (DPSCs) on three different polycaprolactone (PCL) scaffolds. The backbone structure of the scaffolds was manufactured by fused deposition modeling (PCL scaffold). The composition and morphology was functionalized in two of the scaffolds. The first underwent thermal induced phase separation of PCL infused into the pores of the PCL scaffold. This procedure resulted in a highly variable micro- and nanostructured porous (NS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 51 publications
6
50
1
Order By: Relevance
“…Study reported that PCL was suitable for fabrication of scaffold for bone tissue engineering using osteoblasts (27). Recent study reported that PCL scaffold coated with hyaluronic acid and β-TCP mixture supports cell proliferation and cell migration of dental pulp stem cells resulting in even cell dispersion throughout the scaffold (28). It would be interesting to determine if PCL coated with hyaluronic acid and β-TCP mixture can be used as scaffold for DFSCs to improve tissue regeneration in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Study reported that PCL was suitable for fabrication of scaffold for bone tissue engineering using osteoblasts (27). Recent study reported that PCL scaffold coated with hyaluronic acid and β-TCP mixture supports cell proliferation and cell migration of dental pulp stem cells resulting in even cell dispersion throughout the scaffold (28). It would be interesting to determine if PCL coated with hyaluronic acid and β-TCP mixture can be used as scaffold for DFSCs to improve tissue regeneration in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Different printing technologies were used to develop 3D scaffolds for bone tissue engineering applications (Table ). Fused Deposition Modeling was the most frequently used printing technology as it was employed in 38 studies (Figure ) . Low‐temperature deposition manufacturing was used in 11 studies, selective laser sintering in seven studies, Stereolitography in three studies …”
Section: Resultsmentioning
confidence: 99%
“…PCL, PLA, and PLGA were the most used polymers. PCL was the most used polymer as it was found in 29 articles . PLA was used in 13 studies and PLGA in 14 studies .…”
Section: Resultsmentioning
confidence: 99%
“…Artificial scaffolds must also be biodegradable, allowing extracellular matrix to occupy the empty space when the biomaterial is degraded . Polycaprolactone (PCL) is one of the most widely used U.S. Food and Drug Administration (FDA)‐approved synthetic polymers, as it is highly biocompatible and biodegradable and non‐toxic …”
Section: Introductionmentioning
confidence: 99%